Dual threat of tidal flat loss and invasive Spartina alterniflora endanger important shorebird habitat in coastal mainland China. (15th January 2021) - Jackson, Micha V.; Fuller, Richard A.; Gan, Xiaojing; Li, Jing; Mao, Dehua; Melville, David S.; Murray, Nicholas J.; Wang, Zongming; Choi, Chi-Yeung
Abstract: China's coastal wetlands are critically important to shorebirds. Substantial loss of tidal flats, shorebirds' primary foraging grounds, has occurred from land claim and other processes, and is driving population declines in multiple species. Smooth cordgrass Spartina alterniflora was intentionally introduced to the coast of China in 1979 to promote conversion of tidal flats into dry land and has since spread rapidly. The occurrence of S. alterniflora reduces the availability of foraging and roosting habitat for shorebirds, and may be particularly detrimental in places that have experienced other tidal flat loss. However, the extent to which S. alterniflora is encroaching upon important shorebird habitat throughout coastal mainland China, and its intersection with tidal flat loss, has not been quantified. Here, we i) estimate change in the spatial extent of tidal flats between 2000 and 2015 in coastal mainland China where internationally important numbers of shorebirds have been recorded; ii) map the extent of S. alterniflora coverage in 2015 at the same set of sites; and, iii) investigate where these two threats to important shorebird habitat intersect. Our analysis of remote sensing data indicated a 15% net loss in tidal flat area between 2000 and 2015 across all sites, including a net loss in tidal flat area in 39 of 53 individual sites (74%). Spartina alterniflora occurred at 28 of 53 sites (53%) in 2015, of which 22 sites (79%) also had a net loss in tidal flat area between 2000 and 2015. Combined pressures from tidal flat loss and S. alterniflora invasion were most severe in eastern coastal China. Species highly dependent on migrating through this region, which include the Critically Endangered Spoon-billed Sandpiper and Endangered Nordmann's Greenshank and Far Eastern Curlew, may be particularly impacted. Our results underscore the urgent need to arrest tidal flat declines and develop a comprehensive control program for S. alterniflora in coastal areas of mainland China that are important for shorebirds. Highlights: Tidal flat loss and introduced Spartina alterniflora impact coastal ecosystems. Many coastal shorebirds are threatened and declining from habitat loss. Tidal flat loss occurred at ¾ of important coastal shorebird sites in mainland China (2000–2015). Spartina has invaded > ½ of important coastal shorebird sites in mainland China. Tidal flat protection and spartina control are needed to avert further shorebird declines.